Utilization of Audio Visual Media in Developing Students' Critical Attitudes in History Learning at SMA LabschoolUntadPalu - Andi Salsabila; Misnah; Bau Ratu; Lukman (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The background of this research is because of the curiosity of researchers about the use of audio-visual media used in learning History at SMA LabschoolUntadPalu. This research is a qualitative study which took place at LabschoolUntadPalu High School, Palu City, Central Sulawesi. The subjects of this study were all students of class X IIS at LabschoolUntadPalu High School with a total of 1 class and 20 students, as well as history teachers who teach at UntadPalu High School Labschool. Data collection techniques using observation, interviews and documentation. Data processing techniques are descriptive qualitative. The results of the study show that the process of using audio-visual media in increasing students' critical attitudes in learning history is able to make learning in the classroom more active because using audio-visual media can facilitate the communication process between teachers and students. Audio visual media involves hearing as well as sight in one learning process so that students are able to think creatively, innovatively and critically.